Enhancing piezoelectric effect performance in piezoelectric beam design. - Ahmad Sobri, Aiman Syakir (Universiti Sains Malaysia, 2025)
The utilisation of piezoelectric materials in beam structures has garnered significant attention due to their ability to convert mechanical vibrations into electrical energy. This piezoelectric effect has paved the way for the development of energy harvesters using cantilevered beam structures, incorporating one or two piezoelectric layers mounted on a substrate This project seeks to investigate the influence of different piezoelectric layer materials on the voltage output of such beam structures. The primary focus is on the modelling and simulation analysis of cantilevered beam designs, considering a various of piezoelectric materials. In this paper, we dive into two types of simulation PEH cantilever beam: unimorph and bimorph model. The simulations were done in Ansys workbench software, in which modal analysis, harmonic response and voltage generation were set up and run for both types, and the results were validated from previous paper. It is shown that bimorph have a better result in voltage generation, so the simulation proceeds in bimorph with improvised model to determine the highest voltage generation on eight piezoelectric materials which are PZT-5H, PZT-5A, PZT-8. PZT-4, PZT-26, Lithium Niobate, Lithium Tantalate and Lithium Tetraborate. Since the deformation of the models with different piezoelectric materials have different in frequency obtained, a certain frequency within range for all materials were selected to compare the result. Lithium Niobate have the highest voltage obtained at 196Hz with 5681 millivolts followed by PZT-5A and Lithium Tantalate with 3906 millivolts and 150 millivolts respectively. The outcome of the simulation analysis was generated and interpreted graphically, which shows the model deformation, voltage and the frequency response for all the beams with same weight of load, force and dimensions.